URGENSI PERAN MUI DALAM MENUMBUHKAN KARAKTER ANTI KORUPSI TERHADAP ORMAS KEAGAMAAN - Aminah, Siti; Mahmudah, Siti (Jurnal Pendidikan Islam, 2023)
The purpose of this study was to describe the strategic role of the Indonesian Ulema Council in Kediri City in an effort to foster Anti-corruption character against religious organizations in Kediri City in 2022, what steps are taken by the Indonesian Ulema Council in Kediri City in growing Anti-corruption character against religious organizations in Kediri City in 2022, describe what are the supporting and inhibiting factors of the Indonesian Ulema Council in Kediri City in growing Anti-corruption character against religious organizations in Kediri City in 2022. This research is as a study material, and additional literature of the MUI Kediri work program in fostering character and anti-corruption education in Kediri. The conclusion obtained from this study is from 34 correspondents 35% about 12 people give advice to DPD MUI to provide socialization of MUI Fatwa related to Anti-corruption. 20% about 7 people gave advice to hold anti-corruption Character Education, 15% about 5 people gave advice to DPD MUI Kediri to hold a visit to religious community organizations in Kediri. 12% about 4 people gave suggestions to synergize with other institutions such as the KPK, 9% about 3 people gave suggestions to hold Anti-corruption education seminars 6% about 2 people to hold interactive discussions, 3% about 1 person gave input to be held education and coaching regularly and included in the program of DPD MUI Kediri.